EXO1 is a key gene for lung-resident memory T cells and has diagnostic and predictive values for lung adenocarcinoma - Zhuoqi Li; Xiaoyan Lin; Yuanhui Yang; Mei Tian; Lu Zhang; Fujing Huang; Xiao Wen; Zhigang Wei; Yuan Tian (Scientific Reports)
Abstract Lung adenocarcinoma (LUAD) is a very common and lethal kind of lung malignancy. An increasing number of studies indicated that tissue-resident memory T (TRM) cells played significant roles in anti-cancer immunity. In our previous study, EXO1 was found to be a core gene for TRM cells in the prognosis of LUAD. However, the roles of EXO1 in the tumor microenvironment, and its application in the diagnosis and prognosis prediction of LUAD are still inadequately explored. In this study, the RNA expression, DNA methylation, CNV, somatic mutation data of EXO1, and the corresponding patients’ clinical information from publicly available databases were analyzed using bioinformatic methods. The results were validated through immunohistochemical staining of EXO1 in LUAD samples. The results showed EXO1 was aberrantly highly expressed in LUAD tissues. High expression of EXO1 was a risky factor for LUAD patients. The expression level of EXO1 was associated with many clinical features such as TNM stages. It can also distinguish normal tissues and LUAD tumor tissues accurately. EXO1 expression was correlated with the infiltration of immune cells, and high expression of EXO1 was an adverse effect on LUAD patients receiving anti-PD-1/PD-L1 immunotherapy. Moreover, patients with EXO1 mutation had worse DSS, DFI and PFI.